1992
DOI: 10.1172/jci115688
|View full text |Cite
|
Sign up to set email alerts
|

Direct contact between sympathetic neurons and rat cardiac myocytes in vitro increases expression of functional calcium channels.

Abstract: To test the hypothesis that direct contact between sympathetic neurons and myocytes regulates expression and function of cardiac Ca channels, we prepared cultures of neonatal rat ventricular myocytes with and without sympathetic ganglia. Contractile properties of myocytes were assessed by an optical-video system. Contractility-pCa curves showed a 60% greater increase in contractility for innervated myocytes compared with control cells at 63 mM [Cab (n = efficacy of Bay K 8644 was maintained for at least 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 28 publications
7
38
0
Order By: Relevance
“…Changes in calcium current have been described in neonatal rat cells cultured with or without sympathetic ganglia or neurons. Innervated myocytes show an increase in calcium current of ϳ50% (29,35). Similar studies (44) have reported an increase in sodium current in innervated neonatal rat ventricular cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Changes in calcium current have been described in neonatal rat cells cultured with or without sympathetic ganglia or neurons. Innervated myocytes show an increase in calcium current of ϳ50% (29,35). Similar studies (44) have reported an increase in sodium current in innervated neonatal rat ventricular cells.…”
Section: Discussionsupporting
confidence: 68%
“…In myocardial infarction (17,36) and heart failure (25), a decrease in I to was reported, whereas a stimulation of the sympathetic nervous system was also reported. These observations raise the question as to whether reductions of I to were linked to chronic stimulatory effects of catecholamine (29). Until now, this point received no answer.…”
Section: Discussionmentioning
confidence: 99%
“…Cell suspensions underwent two preplating steps to minimize contamination with nonmyocyte cells; in some experiments, cardiac myocytes were isolated from neonatal rats exactly as described (21). Dissociated cells were placed in culture medium consisting of Dulbecco's modified essential medium, 7.5% fetal calf serum, and 0.1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Dihydropyridine-DHP binding studies were carried out as described previously (Chapados et al 1992;Davidoff et al 1997;Gruver et al 1993;Ogawa et al 1992;Scatchard 1949). A crude ventricular homogenate was placed into ice-cold buffer containing (mM); 50 HEPES, 1 MgCl 2 , 1 EDTA, pH 7.4.…”
Section: Radioligand Bindingmentioning
confidence: 99%